Refractive Index Dispersion and Analysis of the Optical Parameters of (PMMA/PVA) Thin Film - Hamad, Tagreed K (Al-Nahrain Journal of Science, 2018)
The optical characteristics of (PMMA/PVA) thin films are investigated by spectrometric measurements. Sample with different percentage are prepared with constant thickness (110 m) using casting technique. The real (n) and imaginary (k) parts of refractive index and dielectric constant of the thin films are determined. Some important parameters of optical absorption, such as the oscillator energy (E0), dispersion energy (Ed), the average value of oscillator strength (S0), wavelength (0) of single oscillator and the ratio carrier concentration to the effective mass (N/m*) have been evaluated. The values obtained for the high frequency dielectric constant through two procedures are in the range of (6.31-7.35) for all ranges of the different concentrations.